Body Image During Pregnancy in the Era of Coronavirus Disease 2019: The Role of Heterogeneous Patterns of Perceived Social Support - Piȩta, Małgorzata; Rzeszutek, Marcin; Lendzion, Michał; Grymowicz, Monika; Piȩta, Wojciech; Kasperowicz, Agata; Kucharski, Marek; Przybył, Mateusz; Smolarczyk, Roman (Frontiers in Psychology, 2021)
Objective: The aim of this study was to explore the profiles of pregnant women on perceived social support with regard to sociodemographic variables, coronavirus disease 2019 (COVID-19)-related distress issues, and body image. We compared the aforementioned relationships within the study variables between pregnant women and a control group of non-pregnant women. Method: The study sample comprised 345 women, 157 pregnant women, and 188 women in the control group. Participants filled out paper-and-pencil or online psychometric questionnaires to assess the variables analyzed in our research. Results: Latent profile analysis revealed six profiles of pregnant women based on perceived social support, which varied in terms of body image evaluation. The high-support profile differed from the profiles with the lowest scores in all support domains. Significant differences in body image between the profiles of pregnant women and the control group were noted. Conclusion: Understanding the mechanisms through which women can attain more body satisfaction during pregnancy is an important research topic that can inspire planning for more effective psychological help, especially in the context of the COVID-19 pandemic and related psychological distress.